BIOAKUMULASI DAN TRANSLOKASI MERKURI DAN CADMIUM PADA MANGROVE FAMILI RHIZOPHORACEAE DI TAMAN NASIONAL RAWA AOPA WATUMOHAI - Andi Septiana; La Ode Abdul Fajar Hasidu; Analuddin Analuddin (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2016)
ABSTRACT This study aimed to know the bioaccumulation and translocation of heavy metal mercury (Hg) and cadmium (Cd) on mangrove Rhizophora spp grown in Rawa Aopa Watumohai National Park. The heavy metals content of Hg and Cd in vegetative organs of R.mucronata, R.apiculata and R.stylosa were analyzed by using Atomic Absorption Spectrophotometry AAS, while their translocation factor (TF) in mangrove organs were elucidated. The results showed that heavy metal bioaccumulation in mangrove organs varied among mangroves. Heavy metals contents in organs of mangrove Rhizophora mucronata were estimated as 0.492 μg/g for Cd and of 0.085 μg/g for Hg. On the other hand, those of metals contents in R. Apiculata were 4.67 μg/g for Cd and 0.414 μg/g for Hg. Meanwhile heavy metals contents in R. stylosa were 0.796 μg/g for Cd metal and 0.084 μg/g for Hg metal. However, the mangroves of R. mucronata and R. apiculata seemed to ineffective on translocation of mercury metal in their organs as of the values of TF among organs were < 1, while the mangrove R. stylosa seemed to more effective on translocation of Hg and Cd heavy metals in its organs (TF > 1.0). Therefore, each mangrove has different ability to accumulate heavy metals in its organs. Thus, maintenance mangrove diversity is important to reduce heavy metal pollutant and keeping coastal area productivity.Keywords : Heavy Metal Bioaccumulation, Heavy Metal Translocation,                               Mangrove, Rawa Aopa Watumohai National Park